2014
DOI: 10.5897/ajmr2014.6779
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real-time PCR assay for the detection and quantification of Gluconacetobacter diazotrophicus in sugarcane grown under field conditions

Abstract: The objective of this study was to evaluate the viability of real-time polymerase chain reaction (PCR) to detect Gluconacetobacter diazotrophicus in sugarcane inoculated and non-inoculated with diazotrophs which are grown under field conditions. The primer pair PAL5F and PAL5R yielded a specific band of 189 bp using real time PCR with SYBER Green I. This primer pair was the most sensitive one to detect endophytic bacteria in sugarcane plants grown under field conditions and inoculated or not with bacterium. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 43 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Several examples in the literature reported that using Real-Time PCR coupled with trait-based PCR permit the detection of the introduced species, simultaneously evaluating their relative abundance within the microbial community ( Clesceri et al, 1999 ; Babić et al, 2008 ; Couillerot et al, 2010 ; Paulo et al, 2014 ; Canfora et al, 2016 , 2017 ; Mandakovic et al, 2018 ; Tartanus et al, 2021 ). However, the suitability of a polyphasic approach based on DNA-based methods emerged clearly from a 3-year long study on the persistence of two entomopathogenic fungi ( Beauveria brongniartii and B. bassiana ) on two sites ( Canfora et al, 2016 ; Tartanus et al, 2021 ).…”
Section: Overview Of the Methodological Tools To Detect And Monitor Bioinocula In Soil: Challenges Limitations And Controversial Issuesmentioning
confidence: 99%
“…Several examples in the literature reported that using Real-Time PCR coupled with trait-based PCR permit the detection of the introduced species, simultaneously evaluating their relative abundance within the microbial community ( Clesceri et al, 1999 ; Babić et al, 2008 ; Couillerot et al, 2010 ; Paulo et al, 2014 ; Canfora et al, 2016 , 2017 ; Mandakovic et al, 2018 ; Tartanus et al, 2021 ). However, the suitability of a polyphasic approach based on DNA-based methods emerged clearly from a 3-year long study on the persistence of two entomopathogenic fungi ( Beauveria brongniartii and B. bassiana ) on two sites ( Canfora et al, 2016 ; Tartanus et al, 2021 ).…”
Section: Overview Of the Methodological Tools To Detect And Monitor Bioinocula In Soil: Challenges Limitations And Controversial Issuesmentioning
confidence: 99%
“…Among these techniques, qPCR is a sensitive and suitable approach for determining the abundance of functional genes from soil-derived DNA and RNA (Fiorentino et al, 2016), and it has therefore been extensively used to track and quantify inoculated strains in soil systems (Providenti et al, 2009;Timmusk et al, 2009). For instance, Sorte et al (2014) used this method to design specific PCR primers targeting a 16S rRNA variable region to specifically measure the abundance of Gluconacetobacter diazotrophicus following coinoculation with other diazotrophic strains in sugarcane plants grown under field conditions ( Table 3). The validation of employed species-specific primers allow the use of this method to evaluate the occurrence of endophytic diazotrophic G. diazotrophicus species in any soil type and plant tissue.…”
Section: Pcr-based Methodsmentioning
confidence: 99%
“…qPCR has been used to monitor the populations of various types of legume-nodulating rhizobia in the field (Maluk et al 2022 , 2023 ). Only a few long-term studies under field conditions have been performed to monitor the dynamics of PGPR in the rhizosphere soil (Zhang et al 2020 ), roots (Soares et al 2021 , Urrea-Valencia et al 2021 ), or stalks (Fernandes et al 2014 ) of different plants, including maize, Brachiaria grasses, soybean, and sugarcane.…”
Section: Introductionmentioning
confidence: 99%